Multipillarisation remodelled: the role of interest organizations in British and German pension reforms - Ebbinghaus, B (Routledge, 2019)
Recent reforms have responded to demographic ageing and fiscal challenges by shifting toward the multipillarisation of pensions to achieve financial sustainability. Reforms towards privatization and marketization of retirement income provision occurred in Britain and Germany with different pension system legacies. While public opinion supports largely the status quo, the stakeholders, in particular, organized capital and labour, have evolved in their positions towards pension reforms. The analysis seeks to draw out how organized interests have sought to influence mulitipillarisation but also adapted their strategies in the context of increasing financialisation in the two political economies. The position of trade unions, employers’ associations, social advocacy groups and the finance sector has increasingly embraced multipillarisation, earlier and more so in Britain than in Germany. A reversal of pension financialisation seems no longer possible but the inequalities and uncertainties need to be addressed in order to make multipillarisation politically sustainable.